Relationship Between Teaching Strategies and Students’ Academic Performance at Ordinary Level Secondary Schools in Gulu District - Lamaro, Gloria; Anena, Doris Jane (East African Journal of Education Studies, 2024)
This study investigated the relationship between teaching strategies and students’ academic performance at ordinary level secondary schools in Gulu District. The study used cross-sectional design. Three hundred and seventy-five (375) participants were randomly and purposively sampled. Questionnaire and interview were used for data collection. Data analysis for quantitative data was done using SPSS version 16. Content analysis was used to analyse interview data. The results showed that most students prefer presentation, seminars and class assessment. Further, students prefer discussion, brainstorming, demonstration and group work. Majority of teachers however prefer lectures, role-play, project and drill as better teaching and learning strategies. The results also show significant positive correlation between project method and level of academic performance (r (259) = .391, p < .0001), strong positive significant correlation between group discussion and level of academic performance (r (259) = .336, p < .0001), positive association between role play and level of academic performance (r (259) = .315, p < .0001) and significant positive association between storytelling and level of academic performance (r (259) = .310, p < .0001). This indicates that project method, group discussion, role play, storytelling, presentation and drill when practiced can improve academic performance of students in ordinary level secondary schools. Educators should consider implementing more of project, group discussion, role play, storytelling, presentation and drill in their teaching activities